2021
DOI: 10.3390/ijerph18094504
|View full text |Cite
|
Sign up to set email alerts
|

Complications in the Use of Deepithelialized Free Gingival Graft vs. Connective Tissue Graft: A One-Year Randomized Clinical Trial

Abstract: In the treatment of gingival recession, different surgical options have been described: free gingival grafts (FGG), connective tissue Grafts (CTG), and a more recent technique, de-epithelialized free gingival graft (DFGG). They are not procedures exempt from the appearance of complications. Most publications refer to postoperative complications, and there is limited literature regarding the development of late complications (weeks or months). Our working group carried out a study to describe the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…On the other hand, the possible complications associated with DGG is less explored in the current literature. A recent randomized clinical trial by Ripoll et al [ 30 ], however, noted a number of late complications with the use of DGG, including graft reepithelialization, change in graft color, cul-de-sac, epithelial bands, superficial revascularization, epithelial cysts, and bone exostoses. Some of these complications happened in our case as well, which were later resolved with gingivoplasty and laser frenectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the possible complications associated with DGG is less explored in the current literature. A recent randomized clinical trial by Ripoll et al [ 30 ], however, noted a number of late complications with the use of DGG, including graft reepithelialization, change in graft color, cul-de-sac, epithelial bands, superficial revascularization, epithelial cysts, and bone exostoses. Some of these complications happened in our case as well, which were later resolved with gingivoplasty and laser frenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these complications happened in our case as well, which were later resolved with gingivoplasty and laser frenectomy. Ripoll et al [ 30 ] also reported that such complications occurred only with the use of DGG but not with CTG. They concluded that, given the occurrences of late complications, DGG seemed to be a less secure method of treating gingival recession than CTG.…”
Section: Discussionmentioning
confidence: 99%
“…Reepithelialization of the DFG was seen in five cases (15.6%) in the cases with (DFG + CAF), the presence of Cul-de-sac (invagination) was seen in five cases (15.6%) in the cases with (DFG + CAF) and the presence of epithelial bands was seen in five cases (15.6%) in the caes with (DFG + CAF). Discoloration of the grafted area was observed in 15 cases (46.9%) of the cases with (DFG + CAF) and superficial graft revascularization was seen in 10 cases (31.3%) in the cases with (DFGG + CAF) [2,7,25].…”
Section: Discussionmentioning
confidence: 99%
“…Autografts are taken from the patient's own tissues (donor zone) and are placed in another zone where there is a defect in the same patient. Autografts are considered the gold standard in transplantology because, as a rule, they do not cause allergies since there is no antigenicity in these transplants [2]. As autografts during this procedure, the doctor takes the mucous membrane from the donor zone (Maxillary Tuberosity, Palate, Cheek).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the outcome of root covering therapy by using the free gingival graft will not be esthetically successful, as such, from this point of view the conjunctive graft offers better esthetics [52,[56][57][58][59][60]. Currently, even if free gingival grafts have proven to be less effective than subepithelial connective grafts in terms of root coverage, they still retain an advantage: they are simple, several teeth can be treated simultaneously, they have easy tissue manipulation, and can be performed when the adjacent keratinized gingiva is insufficient [52].…”
Section: Methods Of Treatmentmentioning
confidence: 99%